2002
DOI: 10.1086/324479
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Intrinsic Magnetic Moments in Black Hole Candidates

Abstract: We present evidence that the power law part of the quiescent x-ray emissions of neutron stars in low mass x-ray binaries is magnetospheric in origin. It can be very accurately calculated from known rates of spin and magnetic moments obtained from the ∼ 10 3−4 times brighter luminosity at the hard spectral state transition. This strongly suggests that the spectral state transition to the low hard state for neutron stars is a magnetospheric propeller effect. We test the hypothesis that the similar spectral state… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 48 publications
1
48
0
Order By: Relevance
“…Thus the massive compact BH candidates cannot be true BHs. Indeed there are significant amount of observational evidences, that the so-called BH candidates could be ultracompact, ultramagnetized, ultrahot balls of plasma [49][50][51][52][53][54][55]. Recall that the Sun too is a magnetized plasma and the violent eruptions like Coronal Mass Ejection (CME) could be traced to such magnetized plasma ativities.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the massive compact BH candidates cannot be true BHs. Indeed there are significant amount of observational evidences, that the so-called BH candidates could be ultracompact, ultramagnetized, ultrahot balls of plasma [49][50][51][52][53][54][55]. Recall that the Sun too is a magnetized plasma and the violent eruptions like Coronal Mass Ejection (CME) could be traced to such magnetized plasma ativities.…”
Section: Discussionmentioning
confidence: 99%
“…How well our approach fits all observations is a special issue; technical details concerning specific experiments and their accuracy need to be investigated. Here we are able to make only a brief review of basic facts starting with summarizing of light/photon observations described by (48)(49)(50)(51)(52)(53) and already commented in brief.…”
Section: Predictions and Observationsmentioning
confidence: 99%
“…There is a trend in current literature to argue the BH horizon existence in favor of BH models without the horizon origination (see, for example, [49][50][51][52][53][54]), and elsewhere.…”
Section: Motion Of Materials Objects With Non-zero Angular Momentummentioning
confidence: 99%
“…However, in a series of papers Robertson & Leiter have suggested that all of the central objects in galactic black hole candidate XRBs have magnetic moments. The evidence comes from (1) the conclusion that in neutron star binaries the power-law part of the X-Ray flux spectrum arises in the neutron star magnetosphere, where calculations and observations are in close agreement, and the recognition that the same model works for black hole XRBs (Robertson & Leiter 2002); (2) the realisation that a magnetic star collapsing towards its event horizon can be slowed by the radiation pressure ensuing from pair annihilation that itself is a result of pair production by the compressed magnetic field -such a "Magnetospheric, Eternally Collapsing Object" maintains an intrinsic magnetic moment outside its event horizon for orders of magnitude longer than a Hubble time (Robertson & Leiter 2003); (3) models of jets that arise from thin disc interaction with MECOs produce the Radio-IR correlation with Mass and X-Ray luminosity observed in neutron star and Black Hole binaries (and also in AGNs) (Robertson & Leiter 2004).…”
Section: The Robertson-leiter Modelmentioning
confidence: 99%